2012
DOI: 10.1128/jvi.06620-11
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro -Selected Drug-Resistant Varicella-Zoster Virus Mutants in the Thymidine Kinase and DNA Polymerase Genes Yield Novel Phenotype-Genotype Associations and Highlight Differences between Antiherpesvirus Drugs

Abstract: Varicella zoster virus (VZV) is usually associated with mild to moderate illness in immunocompetent patients. However, older age and immune deficiency are the most important risk factors linked with virus reactivation and severe complications. Treatment of VZV infections is based on nucleoside analogues, such as acyclovir (ACV) and its valyl prodrug valacyclovir, penciclovir (PCV) as its prodrug famciclovir, and bromovinyldeoxyuridine (BVDU; brivudin) in some areas. The use of the pyrophosphate analogue foscar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 72 publications
4
32
0
Order By: Relevance
“…In this study, we found this mutation in HSV-1 and HSV-2 clones replicated under pressure of KAY-2-41. Other previously known drug resistance mutations mapped in the TK of HSV-1 and HSV-2 of clinical samples have been also identified here, such as the amino acid substitutions R51W, R222C, V187M, S182N, T288M, and Y173C (13,24,(34)(35)(36)(37)(38)(39)(40)(41). Three amino acid changes in the HSV TK were never reported before, i.e., I235F, Y88C, and M129T.…”
Section: Discussionsupporting
confidence: 71%
“…In this study, we found this mutation in HSV-1 and HSV-2 clones replicated under pressure of KAY-2-41. Other previously known drug resistance mutations mapped in the TK of HSV-1 and HSV-2 of clinical samples have been also identified here, such as the amino acid substitutions R51W, R222C, V187M, S182N, T288M, and Y173C (13,24,(34)(35)(36)(37)(38)(39)(40)(41). Three amino acid changes in the HSV TK were never reported before, i.e., I235F, Y88C, and M129T.…”
Section: Discussionsupporting
confidence: 71%
“…The present study forms the basis for a similar VZV database. Thus, this approach is valuable not only for the characterization of unclear resistance mutations but also for the analysis of novel drug candidates against herpesvirus infections (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Foscarnet, a direct viral DNA polymerase inhibitor, is the drug of choice for patients with disseminated acyclovir-resistant varicella [42]. Cidofovir is recommended for acyclovir-and foscarnet-resistant strains [43]. VZIG is a purified pooled anti-IgG to VZV, and prophylaxis is recommended up to 10 days following VZV exposure in immunocompromised patients [44].…”
Section: Discussionmentioning
confidence: 99%